Pengembangan Model Integrated Crop–Livestock Farming pada Kelompok Tani Organik di Desa Bintoyo, Kecamatan Padas, Kabupaten Ngawi - Anita Solihatul Wahidah; Khamid Ibnu Atthoillah; Ahmad Hasan Yusuf; Imroatul Azizah; Asiske Intan Pratama; Ridho Imam Mudin; Siti Aminah; Clarisa Natasyaffa; Mistina Safriyah; Dwi Wahyu Aditama; Ummii Mawaddaturrof; Hanafi Abdul Aziz; Lexintya Kanisha Dahuri (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Integrated crop–livestock farming (ICLF) offers a pathway toward sustainable agriculture by closing the nutrient loop between cattle rearing and rice cultivation at the smallholder level. This community-based action research was conducted with an organic farmer group in Bintoyo Village, Padas Sub-district, Ngawi Regency, East Java, using a Participatory Action Research (PAR) approach comprising four cycles: plan, act, observe, and reflect. Four interrelated main programs were implemented: (1) mentoring on beef cattle fattening management, covering breed selection, feeding schedules, sanitation routines, and first-aid disease handling; (2) processing of cattle manure and urine waste into liquid organic fertilizer based on local microorganisms (MOL) and solid compost; (3) application of the resulting organic fertilizer on irrigated rice fields; and (4) construction and installation of barn owl (Tyto alba) nest boxes as an environmentally friendly biological control of rice field rats. Researchers were embedded throughout every field stage, from the initial audit to the reflective evaluation, functioning as co-researchers alongside the farmer group rather than as external experts. Reflective evaluation indicates measurable improvement in cattle husbandry practices, an operating on-farm fertilizer production cycle, improved soil and plant vigor indicators on treated rice plots, and the early establishment of owl nest-box occupancy as part of integrated pest management. This activity validates the integration of PAR with the ICLF framework as a replicable, low-cost model of sustainable agriculture for rice–cattle smallholder communities in Indonesia.